The Effectiveness of ICT-Related Training in Increasing the Competence of Vocational School Teachers - Zulvia Trinova; Abdul Wahab; Catur Budi Susilo; Pandu Adi Cakranegara; Ichsan Ichsan (AL-ISHLAH: Jurnal Pendidikan, 2023)
Vocational schools are specifically designed to produce graduates ready for the job market and industry. In vocational schools, teachers have an important position. Therefore competency development is a must related to ICT. This study describes the effectiveness of ICT competency development training and its correlation to vocational teachers' competence. The research method is carried out by reviewing relevant previous studies and then drawing a result and conclusion. There are two main results of this research. First, ICT-related training has a positive influence on the competence of teachers as participants. Second, the positive impact of training is only felt on a small scale, so that teacher competence on a large scale (Indonesia) still needs to be improved.